Managing software deliverables a software development management methodology - Rittinghouse, John W. (Amsterdam : Elsevier ; Boston : Digital Press, 2004)
Managing Software Development describes a set of proven processes for establishing an effective Software Program Management Office (SPMO) function in a corporate setting. Every business that has people performing Software Project Management (PM) activities has a need for these processes. In some instances, an organization may already have a PMO chartered with overall responsibility for each project managed in an enterprise. In those cases, this book will either provide validation of their efforts or it will provide some techniques and useful approaches that can be utilized to further improve on their overall implementation of the PMO. In the vast majority of cases in business, however, a PMO is unheard of. Each project managed in the enterprise is unfortunately managed separately from all others (at great cost in both time and money to the enterprise). The book provides a downloadable "drop-in" web site containing every type of template needed to perform the activities described here. *Phase Roadmaps clearly depict what is expected by all parties at each phase of effort *Pre-built Intranet is ready to deploy in a corporate setting and provides immediate use *Process Methodology adheres to proven best-practices for software development.
Understanding the SPMO -- SEP phase I : initiation -- SEP phase II : analysis and detailed planning phase -- SEP phase III : detailed design phase -- SEP phase IV : construction phase -- SEP phase V : testing -- SEP phase VI : implementation -- SEP phase VII : support phase -- SEP phase VIII : project closeout -- Project wizardry 101 -- Some software best practices to consider -- Putting it all together.
Includes bibliographical references and index.
Keywords: Computer software -- Development -- Management; Computer programming -- Management; Project management; Electronic books